Os ethe dos oradores em diferentes gêneros do direito processual civil - Lovo, Letícia Machel (2017)
The current work was born of the union between Brazilian Civil Procedural Law and rhetorical studies. Taking as corpus a process composed by four distinct textual genres, we find, in rhetoric, a way to analyze the speaker's ethos in each piece present in the selected process. The genres that make the corpus are: The Initial Petition, the Contest, the Sentence, and, finally, the Judgment. Under the lens of rhetorical studies, we will try to understand how the different ethos manifested by the orators act in each analyzed genre. Based on the theoretical structure present in the works of Aristotle and Meyer, concerning rhetoric, and of Bakhtin, Marcuschi and Costa, regarding the study of genres, we will seek to know the selfimage presented by each speaker when drafting his procedural piece. In addition, we will consider the possible passions (pathos) awaked in each auditorium considered as a function of the speaker's ethical behavior. Still in this area, we will consider the rhetorical tripod (ethos, pathos and logos), as well as the virtues of the ethos (phronesis, arete and eunoia) in search of understand the stages of the argumentative process and the parts of the rhetoric discourse relevant to the analysis, together with their respective deployments in each procedural piece. We find, therefore, by the ethical analysis of the image of the speakers that in the initial petition, the attribute of phronesis prevails, in the Context, the species phronesis and arete ties, in the Sentence, we see the exacerbated use of arete and finally, in the Judgment we have predominantly the ethos of phronesis. These results showed us that, although society and the judiciary defended the idea that decisions should be impartial and predominantly weighted, we know that the personal valuation of the individual translates into his words in the text, leaving perceptible marks. Thus, we have had the example that the same fact can be seen, interpreted and judged in different ways, which makes rhetoric preponderate and end up playing a major role in legal discourse. We believe, for this reason, that the present research can contribute to a better understanding of the relations between rhetorical ethos and textual genre, especially regarding the genres of the judicial sphere.